Operational Plan Analysis in Bina Insani University Business Development Project at Cikarang Campus - Luthvi Rachman Ervianto; Tantri Yanuar Rahmat Syah; Suwarto; Rhian Indradewa (Jurnal Syntax Transformation, 2024)
Bina Insani University's business development on the Cikarang campus will require good operations to run according to plan. Therefore, operational plan analysis is needed in the Bina Insani University business development project on the Cikarang campus. The aim of this research is to analyze the operational plan in the Bina Insani University business development project on the Cikarang campus. This study used qualitative research methods. Data collection techniques in this research used literature study and observation. The data that has been collected is then analyzed thematically. The research results show that the operational plan for the Bina Insani University business development project on the Cikarang campus has been well prepared. This operational planning is carried out through several stages including the physical construction of Bina Insani University campus buildings, Cikarang Campus, implementation of learning operations, service design and operational delivery.